The complete mitochondrial genome of the Eurasian wryneck Jynx torquilla (Aves: Piciformes: Picidae) and its phylogenetic inference - Du, Chao; Liu, Li; Liu, Yunpeng; Fu, Zhaohui (Zootaxa, 2020)
The Eurasian Wryneck is a species of wryneck woodpecker breeding in temperate regions of Europe and Asia. We sequenced the mitochondrial genome of Jynx torquilla (Aves, Piciformes, Picidae) using the next generation sequencing. The circular genome is 16,832 bp long, encoding 13 protein-coding genes (PCGs), 22 transfer RNAs (tRNAs), two ribosomal RNAs (rRNAs), and two control regions. Gene order and orientation are similar to the most common type suggested as ancestral for birds but have a 1,221 bp control region and a 60 bp remnant control region. Phylogenetic analyses of 17 piciform taxa, based on both nucleotide and amino acid sequences of mitochondrial PCGs, strongly support the monophyly of Picidae. All phylogenetic trees indicate that the subfamily Jynginae is a monophyletic lineage sister to other woodpeckers, including monophyletic Picinae. Only the Bayes inferred tree based on the nucleotide dataset, recovered Picumninae as monophyletic. These findings will be helpful for the understanding of the phylogeny and evolution of Picidae.